Chapter 1: The Copenhagen Process: Principles and Guidelines. (2nd February 2015) - Hartmann, Jacques
Abstract: This article analyses the outcome of the 'Copenhagen Process on the Handling of Detainees in International Military Operations': a five-year multi-stakeholder effort to develop principles and good practices on detention in international military operations. The Process concluded in 2012 when 18 States 'welcomed' a set of non-binding 'Principles and Guidelines.' The Principles and Guidelines address uncertainties surrounding the legal basis for the detention, treatment, and transfer of detainees during international military operations, drawing on both human rights and international humanitarian law. This article comments on the Principles and Guidelines, shedding some light on the context in which they were developed and adopted.